Solvothermal synthesis of superhydrophobic hollow carbon nanoparticles from a fluorinated alcohol. Issue 38 (15th September 2015) - Lyth, S. M.; Ma, W.; Liu, J.; Daio, T.; Sasaki, K.; Takahara, A.; Ameduri, B.
Abstract : A new and simple method of synthesizing fluorinated carbon at the gram scale is presented by reacting a fluorinated alcohol with sodium at elevated temperatures in a sealed Teflon reactor. Abstract : A new and simple method of synthesizing fluorinated carbon at the gram scale is presented by reacting a fluorinated alcohol with sodium at elevated temperatures in a sealed Teflon reactor. The resulting carbon nanoparticles are around 100 nm in diameter, and display a hollow shell morphology, with a significant amount of fluorine doped into the carbon. The nanoparticles disperse easily in ethanol, and are thermally stable up to 400 °C and 450 °C under air and nitrogen, respectively. The nanoparticle dispersion was printed onto various substrates (paper, cloth, silicon), inducing superhydrophobicity.